The effect of neuromuscular warm-up on balance and ankle mobility among Physically active females involved in pivoting team sports - Zamri, Puteri Nur Aisyah Mohd (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
The purpose of this study is to investigate the effectiveness of neuromuscular warm-ups on balance and ankle mobility. To date, studies investigating the effects of neuromuscular warm-up on the risk of ankle injuries (measured through balance and ankle mobility), especially on females, are very limited. Thus, this study was carried out. Twenty physically active females in Universiti Sains Malaysia participated in pivoting team sports; netball, basketball, frisbee, field hockey, and soccer were recruited. They were distributed randomly to one of these two groups: neuromuscular warm-up group, NWU (n=10) or general warm-up group, GWU (n=10). The intervention was executed for 6 weeks where, participants in the NWU group performed dynamic exercise which include 20-meter running, balance, plyometrics, and strengthening. Meanwhile, participants in the GWU group performed static stretching which includes hamstring stretch, quadriceps stretch, gastrocnemius stretch, adductor stretching (butterfly stretch), and iliopsoas stretching (lunge stretch). The pre and post-test measurements were conducted on both legs, with average readings recorded for the Single Leg Balance (SLB) test for body balance assessment and Dorsiflexion Long Test (DLT) for ankle mobility assessment. Mixed ANOVA was used to analyse the data. As a result, between-group effects showed that balance and ankle mobility were not significantly different (p>0.05) between NWU and GWU groups. Within-group effects showed that GWU has no significant effects (p>0.05) on all the parameters measured. However, the NWU group showed a significant increase in balance and ankle mobility from pre to post-test. Thus, it can be concluded that 6 weeks of the neuromuscular warm-up program were effective in reducing ankle injury risk through improving ankle balance and ankle mobility of the athletes involved in pivoting team sports.